The role of intra‐operative cell salvage in patient blood management for revision hip arthroplasty: a prospective cohort study. (9th February 2020) - Palmer, A. J. R.; Lloyd, T. D.; Gibbs, V. N.; Shah, A.; Dhiman, P.; Booth, R.; Murphy, M. F.; Taylor, A. H.; Kendrick, B. J. L.; ,
Summary: Cell salvage is an important component of blood management in patients undergoing revision hip arthroplasty surgery. However concerns regarding efficacy and patient selection remain. The aims of this study were to describe intra‐operative blood loss, cell salvage re‐infusion volumes and red blood cell transfusion rates for revision hip procedures and to identify factors associated with the ability to salvage sufficient blood intra‐operatively to permit processing and re‐infusion. Data were collected from a prospective cohort of 664 consecutive patients undergoing revision hip surgery at a single tertiary centre from 31 March 2015 to 1 April 2018. Indications for revision surgery were aseptic (n = 393 (59%)) fracture (n = 160 (24%)) and infection (n = 111 (17%)). Salvaged blood was processed and re‐infused when blood loss exceeded 500 ml. Mean (SD) intra‐operative blood loss was 1038 (778) ml across all procedures. Salvaged blood was re‐infused in 505 of 664 (76%) patients. Mean (SD) re‐infusion volume was 253 (169) ml. In total, 246 of 664 (37%) patients received an allogeneic red blood cell transfusion within 72 h of surgery. Patients undergoing femoral component revision only (OR (95%CI) 0.41 (0.23–0.73)) or acetabular component revision only (0.53 (0.32–0.87)) were less likely to generate sufficient blood salvage volume for re‐infusion compared with revision of both components. Compared with aseptic indications, patients undergoing revision surgery for infection (1.87 (1.04–3.36)) or fracture (4.43 (2.30–8.55)) were more likely to generate sufficient blood salvage volume for re‐infusion. Our data suggest that cell salvage is efficacious in this population. Cases where the indication is infection or fracture and where both femoral and acetabular components are to be revised should be prioritised.